Chemical constituents derived from Artocarpus xanthocarpus as inhibitors of melanin biosynthesis. (September 2015) - Jin, Yu-Jing; Lin, Cha-Chi; Lu, Tzy-Ming; Li, Jih-Heng; Chen, Ih-Sheng; Kuo, Yueh-Hsiung; Ko, Horng-Huey
Abstract : Graphical abstract: Six previously unknown compounds and 18 known compounds from Artocarpus xanthocarpus were isolated and characterized spectroscopically. Their anti-melanogenesis activity were evaluated in B16F10 melanoma cells. The results indicated that some of these constituents may be a candidate for the depigmentation agents. Highlights: Six previously unknown flavonoids and 18 known compounds were isolated from Artocarpus xanthocarpus . Stilbene oligomer derivative was discovered and a biosynthesis pathway is proposed. Antioxidant and anti-melanogenesis activity of isolated compounds were evaluated. A. xanthocarpus is potentially useful for treating hyperpigmentation. Abstract: Twenty-four compounds, including the previously unknown artoxanthocarpuone A, artoxanthocarpuone B, hydroxylakoochin A, methoxylakoochin A, epoxylakoochin A, and artoxanthol, were isolated and characterized spectroscopically. Among them, artoxanthol is stilbene oligomer presumably constructed in a 5, 11, 12-triphenyl hexahydrochrysene scaffold by a Diels–Alder type of reaction, for which a biosynthetic pathway is proposed. Artoxanthol, alboctalol, steppogenin, norartocarpetin, resveratrol, oxyresveratrol, and chlorophorin potently inhibited mushroom tyrosinase activity with IC50 values from 0.9 to 5.7 μM that were all far stronger than the positive controls. Artoxanthocarpuone A, artoxanthocarpuone B, methoxylakoochin A, lakoochin A, cudraflavone C, artonin A, resveratrol, and chlorophorin reduced tyrosinase activity and inhibited α-melanocyte-stimulating hormone-induced melanin production in B16F10 melanoma cells without affecting cell proliferation. Collectively, the results suggest that the constituents of Artocarpus xanthocarpus have potential to be used as depigmentation agents.